Energy Policy, Regulation and Sustainable Development - Mentel, Grzegorz; Majewski, Sebastian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is mainly aimed at economists involved in the energy market. Energy market processes have an enormous impact on people's day-to-day economic activities. The economics of sustainability leads the way in theorizing how best to prevent environmental degradation whilst also fostering positive economic development. For these reasons, the focus of this reprint is mainly on pollution and the energy transition. Works on energy resources and future-oriented solutions that reduce the consumption of classical energy resources are explored in the reprint. Papers relating to contemporary accounting and the stock market are also presented. The geographical area of the works showcased here essentially covers the entire eastern hemisphere of the globe (Asia, Africa and Europe). They are mainly empirical studies, although in one case a bibliometric analysis is included.